Spunti di riflessione bioetica dalla letteratura - Giardina, Simona; Mele, Vincenza (Medicina e Morale, 2010)
L'articolo focalizza l'importanza di un dialogo tra bioetica e letteratura. Entrambe rivendicano ciò che manca o è andato perduto nella pratica medica e che riguarda soprattutto la relazione medico-paziente. L'intento è quello di far emergere il ruolo attivo della letteratura nella riflessione biomedica. L'introduzione nei curricula delle Facoltà di Medicina di speciali moduli didattici dedicati alle Scienze Umane non ha come fine solo l'arricchimento intellettuale della professione ma persegue una finalità rigorosamente operativa. Il vantaggio della letteratura è quello di trasmettere informazioni in forma umana, di farci avvicinare all'umanità degli altri, diminuendo la distanza tra noi e l'altro. La letteratura tocca i nostri cuori e allo stesso tempo le nostre menti. Dialogare con la letteratura e con le Scienze umane in genere può aiutare a sviluppare capacità quali l'osservazione, l'analisi, l'empatia, lo spirito critico, fondamentali nella pratica medica. Attraverso la lettura di testi significativi il futuro medico incontrerà il lato umano della medicina: la comprensione del malato nella sua unicità, la dimensione esistenziale della malattia, l'importanza del recupero di un dialogo profondo tra medico e paziente. ———- The aim of this work is to highlight the importance of the dialogue between very different disciplines trying to bring to light the value and function of literature vis-à-vis bioethical concerns. One of the main areas where literature and bioethics coalesce in important literary texts is the relationship between humankind and sickness (with particular regard on doctor-patient relationship). This paper focalizes the anthropological and ethical aspects of this relationship. The intention is to encourage not just aesthetic experience but human experience of this relationship. The way in which literature deals with these aspects shows a great level of humanity and empathy. It is just by this way that the reader is fully immersed in that specific problem. Literature has a great power to awaken us to the humanity of others decreasing the distance between them and us. Literature can touch our hearts at the same time our heads. Literature provides insight into the human condition, suffering, personhood and offer a historical perspective on medical practice. Attention to literature and the arts helps to develop and nurture skills of observation, analysis, empathy and self-reflection - skills that are essential for human medical care. Through the poems, stories and essays, students will appreciate their roles not just as healers or caregivers but as compassionate human beings. They will see the importance of fostering the human side of medicine: understanding the needs of patients as unique individuals, expressing compassion and empathy in the face of tragedy and grief and making judgments in complex ethical situations.